Pengaruh Akuntansi Pertanggungjawaban, Kompetensi Sumber Daya Manusia dan Komitmen Organisasi terhadap Kinerja Hotel Berbintang - Sumariyani, Ni Made Ria; Kurniawan, Putu Sukma (Universitas Pendidikan Ganesha, 2020)
This type of research is a quantitative study whose data sources come from primary data in the form of dissemination of questionnaires to respondents through a survey method aimed at reviewing variables that affect the performance of the hotel. The population in this study is all star hotels in Buleleng Regency. The selected sample uses purposive sampling technique and obtained a sample amount of 60 samples. Data analysis techniques consist of: Descriptive statistic analysis, data quality tests, classical assumption tests, and hypothesis testing. Where the hypothesis test includes multiple linear regression tests, the T-Test and Coefesien test determinations with the help of SPSS version 24 for Windows. The results of this study show that, 1. Accounting accountability has a positive effect on the performance of star hotels in Buleleng Regency, 2. Human Resources Competency has a positive effect on the performance of star hotels in Buleleng Regency and 3. Organizational commitments positively influence the performance of star hotels in Buleleng Regency